2019
DOI: 10.1016/j.rcim.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer path planning control for the simulation of manipulation tasks: Involving semantics and topology

Abstract: layer path planning control for the simulation of manipulation tasks : involving semantics and topology. (2019) Robotics and Computer-Integrated Manufacturing, 57. 17-28.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…These rigid bodies are built on CAD models. Recently, the environment model proposed by Cailhol et al [12] consists of a rigid bodies model and a free-space model. Both of them involve different levels based on semantic, topologic, and geometric information.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…These rigid bodies are built on CAD models. Recently, the environment model proposed by Cailhol et al [12] consists of a rigid bodies model and a free-space model. Both of them involve different levels based on semantic, topologic, and geometric information.…”
Section: State Of the Artmentioning
confidence: 99%
“…Mozos et al [43] propose to construct spatial regions by detecting doorways. Cailhol et al [12] define a topological graph to seize the connectivity of the free space in the environment. The graph connects places to cross and borders to reach; the places and borders are automatically extracted from a geometric model of the free space using an octree, by using a process inspired by region-growing algorithms used in computer vision [23].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the assembly plan, the next typical step is path planning for each of the assembly steps, to move the robot to pick up the next part, transport the part to the assembly position, and execute the assembly motion (and action, e.g., with a screwdriver). For most assembly scenarios in factory automation, the path planning is carried out solely based on kinematicsmanually, by teaching the robot, or automatically, based on generated collision-free paths from kinematic simulations (Cailhol et al 2019).…”
Section: Modelling and Assembly Simulation In Industrial Contextsmentioning
confidence: 99%
“…When it comes to trajectory planning, purely geometrical models may become computationally costly for severely constrained environments or complex products. It has been shown that incorporating higher-level abstractions involving multilayer environment models containing semantic and topological aspects within a global planner may alleviate the foregoing issue, where the initial coarse model is locally refined based on semantically characterized geometry [69]. On the other hand, knowledge transfer frameworks enable platforms allow already acquired information regarding e.g.…”
Section: F Alleviating the Computational Burdenmentioning
confidence: 99%